Donor–Acceptor Nanocarbon Ensembles to Boost Metal‐Free All‐pH Hydrogen Evolution Catalysis by Combined Surface and Dual Electronic Modulation. (17th September 2019) - Yang, Meijia; Zhang, You; Jian, Junhua; Fang, Long; Li, Jing; Fang, Zhengsong; Yuan, Zhongke; Dai, Liming; Chen, Xudong; Yu, Dingshan
Abstract: A combined surface and dual electronic modulation strategy is used to realize metal‐free all‐pH catalysis towards the hydrogen evolution reaction (HER) by coupling a N‐doped carbon framework (MHCF, electron acceptors) derived from MOFs with higher‐Fermi‐level pure carbon nanotubes (CNTs, electron donors), followed by surface modification with carboxyl‐group‐rich polymers. Although the three constituents are inactive, as‐assembled ternary membranes yield superior HER performance with low overpotentials and high durability (≤5 % activity loss over 100 h) at all pH values. The C adjacent to pyrrolic N in MHCF is the most active site and the induced directional interfacial electron transfer from CNTs to MHCF coupled with N‐driven intramolecular electron transfer in MHCF optimizes Gibbs free energy for hydrogen adsorption (Δ G H* ) near zero, while the polymer modulation enables local H + enrichment in acidic media and enhanced water adsorption and activation in neutral and basic media. Abstract : Stabil, metallfrei und pH‐universell ist ein Katalysator zur H2 ‐Entwicklung, der durch die Verknüpfung von N‐reichem Kohlenstoff (MHCF) mit reinen Kohlenstoffnanoröhren hergestellt wurde. Im MHCF wird ein kombinierter intra‐/intermolekularer Elektronentransfer induziert, und die Oberflächenmodulation mit carboxylreichen Polymeren führt zur Protonenanreicherung bei pH 0 und verstärkten H2 O‐Adsorption und Aktivierung bei pH 7 und 14.